Rebels & redcoats [videorecording (DVD)] : how Britain lost America - Lilley, Harvey; Holmes, Richard, 1946-2011 (PBS Home Video ; Distributed by Paramount Home Entertainment, 2004)
An exploration into America's Independence War. Using interviews with scholars, first-person narratives and historic documents, the series travels back to the passionate, violent and sometimes tragically funny events of the 1770s.